(untitled) (Huellas, 2021)
The initial and continuous teacher training process cannot be thought without the exercise of continuous reflection. In other words, training and reflection are permanently linked and in a relationship that can be considered as one of mutual dependence, where both are favored as long as feedback takes place. For this reason, reflection is "transformative" (Souto, 2016). This article is a didactic contribution to the interpretation of the place of reflection in the continuous teacher training process from the perspective of several leading authors in the didactic literature. In this sense, it is intended to highlight the purposes of this action for the transformation and improvement of practices, with special emphasis on its epistemological and ethical dimension. As a resulting proposal, a model is presented, the reflective cycle, which allows us to rethink the class in order to reconstruct it with a positive sense.